Spirituality/Faith Integration and Career Sustainability: A Phenomenology of African-American Principals in U.S. Urban High-poverty Public Schools - Hicks, Susan G. (Journal of management, spirituality & religion, 2024)
A phenomenological lens was used to analyze themed patterns to understand how spirituality provides hope, a sense of purpose, and resiliency, enabling 12 Christian African- American principals of urban public schools in the United States to sustain their careers while facing marginalization, inequities, economic oppression, and stress. The terms spirituality and faith are used interchangeably. Both terms refer to what it means to be human and both incorporate self-transcendence to make sense of lived experiences by communicating with a higher source. Findings reveal that spirituality is an important resource that supports career sustainability for Christian African-American principals who lead U.S. urban public schools. In particular, this article provides critical voices of educational leaders, from urban high-poverty public school contexts, who integrate their spirituality/faith within their leadership role. The article helps to fill the literature gap in workplace spirituality, educational leadership, and career sustainability and offers implications for scholars and practitioners.